(untitled) (Research, Society and Development, 2022)
Diets, as well as other slimming practices, are means that, when used for a certain purpose, may or may not harm the health of individuals. As an example of a harmful procedure, there are dietary restrictions which are used by martial arts athletes. According to the rules of the sport, they need minimum and maximum weights to compete, leading them to follow these and other extreme strategies to reach the goal of decreasing body weight. The objective of this literature review, in turn, was to choose materials related to the consequences and strategies used by athletes to lose weight quickly with reference to the main weight loss methods, dietary restrictions and dehydration of this public in the pre-competition period, correlating with the importance of food and nutritional reeducation for these fighters. Therefore, this study was carried out through a review of the literature with research that contained data regarding eating behavior, weight loss strategies and their consequences in fighting athletes. After reviewing the literature, it was better understood about the habits of athletes, as well as the damage that these methods cause. To compose the study, articles were selected according to their relevance and exploration of the proposed theme, based on the last ten years.